Left Modified Orbitozygomatic Approach for Clipping of Multilobulated Middle Cerebral Artery Bifurcation Aneurysm: 2-Dimensional Operative Video. Issue 4 (17th June 2020) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Middle cerebral artery (MCA) aneurysms are associated with one of the most favorable approaches for microsurgical treatment; however, aneurysm geometrics can pose challenges during clip application. The surgeon must be mindful of the clip configuration options available during the planning of ideal clip occlusion for irregular or multilobulated aneurysm domes. This patient had an incidental multilobulated MCA bifurcation aneurysm and underwent an orbitozygomatic approach for microsurgical treatment. Proximal and distal control of the aneurysm were achieved, and complete clip occlusion was achieved following the placement of a single permanent clip. Flow within the parent vessel was well preserved, and complete aneurysm occlusion was achieved. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona.